Diagnostic value of donor‐derived cell‐free DNA to predict antibody‐mediated rejection in donor‐specific antibody‐positive renal allograft recipients. (26th August 2021) - Mayer, Katharina A.; Doberer, Konstantin; Tillgren, Amanda; Viard, Thierry; Haindl, Susanne; Krivanec, Sebastian; Reindl‐Schwaighofer, Roman; Eder, Michael; Eskandary, Farsad; Casas, Silvia; Wahrmann, Markus; Regele, Heinz; et al.
Summary: Circulating donor‐specific antibodies (DSA) do not necessarily indicate antibody‐mediated rejection (ABMR). Here, we evaluated the diagnostic value of donor‐derived cell‐free DNA (dd‐cfDNA) as an add‐on to DSA detection. The study included two independent cohorts of DSA + kidney allograft recipients, 45 subclinical cases identified by cross‐sectional antibody screening (cohort 1), and 30 recipients subjected to indication biopsies (cohort 2). About 50% of the DSA + recipients had ABMR and displayed higher dd‐cfDNA levels than DSA + ABMR − recipients (cohort 1: 1.90% [median; IQR: 0.78–3.90%] vs. 0.52% [0.35–0.72%]; P  < 0.001); (cohort 2: 1.20% [0.82–2.50%] vs. 0.59% [0.28–2.05%]; P  = 0.086). Receiver operating characteristic (ROC) analysis revealed an area under the curve (AUC) of 0.89 and 0.69 for dd‐cfDNA, and 0.88 and 0.77 for DSA mean fluorescence intensity (MFI), respectively. In combined models, adding dd‐cfDNA to DSA‐MFI or vice versa significantly improved the diagnostic accuracy. Limited diagnostic performance of dd‐cfDNA in cohort 2 was related to the frequent finding of other types of graft injury among ABMR − recipients, like T cell‐mediated rejection or glomerulonephritis. For dd‐cfDNA in relation to injury of any cause an AUC of 0.97 was calculated. Monitoring of dd‐cfDNA in DSA + patients may be a useful tool to detect ABMR and other types of injury. Abstract : Analyzing two independent cohorts of kidney allograft recipients, we found that detection of donor‐derived cell‐free DNA as an add‐on to donor‐specific antibody detection may be a useful non‐invasive surveillance tool to uncover antibody‐mediated kidney allograft rejection.